COUPLED DEGASSING AND CRYSTALLIZATION: EXPERIMENTAL STUDY AT CONTINUOUS PRESSURE DROP, WITH APPLICATION TO VOLCANIC BOMBS - Simakin A.G.; Epel'baum M.B.; Armienti P. (My University, 1999)
Experiments on degassing of water-saturated granite melts with a pressure drop from 100 and 450 MPa to 40 and 120 MPa, respectively, at temperatures close to feldspar liquidus (750–700  °C), were carried out to determine the modality of water exsolution and vesicle formation at the liquidus temperature. Pressure-drop rates as small as approximately 100 bar/day were used. Uniform space distributions of bubbles of exsolved water were obtained with starting glass containing a small fraction (≈0.5 vol.%) of trapped air bubbles. Volume crystallization of feldspar was observed in degassed melts supplied with seeds. Bubble size distributions (BSD) measured in granite glasses after degassing are presented. Data on vesicle characteristics (number, radius, area, elongation) were acquired on images digitized with standard software, while the reconstruction of size distributions was performed with the Schwartz-Saltikov "unfolding" procedure. Bubble size distributions of size classes in the range 5–1000 μm were acquired with proper magnification and satisfactory statistical reliability of determined number densities. The BSDs of the experimental samples are compared with the results of measurements of rapidly degassed products of Mt. Etna and Vulcano Island. Many particular features of the bubble nucleation and growth can be distinguished in an individual BSD. However, the general BSD of the whole data set, including natural ones, can be relatively well described with linear regression in bilogarithmic coordinates. The slope of this regression is approximately 2.8±0.1. This dependence is in striking contrast with distributions theoretically predicted with classical nucleation models based on homogeneous nucleation of vesicles. The theoretical distribution requires the occurrence of strong maxima that are not observed in our experimental and natural samples, thus arguing for heterogeneous nucleation mechanisms.